Clinical Characteristics and Pulmonary Computerized Imaging Findings of Critically Ill Egyptian Patients with Multisystem Inflammatory Syndrome in Children. (April 2022) - Ibrahim, Hanan M.; Mohammad, Shaimaa Abdelsattar; Fouda, Eman; Abouelfotouh, Khaled; Habeeb, Neveen M.; Rezk, Ahmed Rezk; Magdy, Sondos; Allam, Ahmad M.; Mahmoud, Sanaa A.
Objectives. This study was carried out to delineate the patients' characteristics and the imaging findings and their relation to some biochemical markers of 31 critically ill patients with MIS-C. Design. A retrospective cross-sectional study including all critically ill MIS-C patients admitted to the PICU from June 23rd to July 22nd, 2020. Results. Eighteen males and 13 females, with a median age of 9 years (interquartile range 6-11) presented mainly with fever (100%) and hypotension (100%). Abnormalities in the chest computed tomography were detected in 22 cases (71%). Consolidation and architecture distortion were detected in 58.1% of patients; bilateral lesions and lower lobe infiltrates, each, was evident in 64.5% of patients, while the peripheral distribution of lesions was seen in 71% of the cases. Pleural thickening and effusion, each, was found in 51.6% of the patients. In this small case series, the presence of high ferritin was significantly associated with the bilaterality of the lesions. Elevated C-reactive protein was associated with the peripheral distribution of the lesions. Thrombocytopenia and hypoalbuminemia were significantly correlated with the CT disease stage and CT severity score respectively. Conclusions. Although a few children in this group of MIS-C patients presented with respiratory manifestations, yet, most of them demonstrated significant radiological lung involvement, which necessitates a longer-term follow-up.